Pelaksanaan Partisipasi Masyarakat Dalam Proses Pembentukan Peraturan Daerah (Studi Di Kota Mataram) - Irawan Kusumahadi; Kaharudin Kaharudin; Muh Risnain (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2021)
This paper is to examine the implementation of community participation in the process of forming regional regulations in Mataram City. This study uses a sociological (empirical) juridical legal research method with a statutory approach and a sociological approach. The results of the study show that the implementation of community participation in the process of forming regional regulations in Mataram City using information technology channels through an application called Partner (community participation in the formation of regional regulations) based on mobile phones, is considered to be able to overcome obstacles in the manual participation process. has not been fully implemented in accordance with the provisions of laws and regulations, especially in fulfilling the provisions for the involvement of the community in the process of forming regional regulations which refer to Article 354 Paragraph (1), (3), (4) and (5) Law Number 23 Year 2014 regarding Regional Government as amended several times, most recently by Law Number 9 of 2015 and Article 2, 3 and Article 4 of Government Regulation Number 45 of 2017 concerning Community Participation in the Implementation of Regional Government, because the application is not supported by the legality of its utilization and human resources who manage the application. So that the implementation of community participation in the process of forming regional regulations in the City of Mataram has not been maximal and the resulting regional regulations cannot be said to have a responsive legal character.